Hverken lighed eller anerkendelse? Kvinder, mænd og skattelovgivning i Danmark - Ravn, Anna-Birte (Kvinder, Køn & Forskning, 2005)
Taking its point of departure in Nancy Fraser’s redistribution-recognition dilemma, the article analyses the gendered impact of the Danish tax system 1903-83 and the debates over reform of the system during the formative years of the Danish welfare state, i.e. in the 1950s and 1960s. The author shows how tax laws since the early 20th century contributed to constructing a male breadwinner/female housewife family norm and how the female opponents of the gendered tax system – organized in the Danish Women’s Society, the National Council of Women in Denmark, Social Democratic Women’s Committees and the Federation of Danish Trade Unions – were caught in a dilemma between socio-economic redistribution in favour of labouring married women on one side and cultural recognition of women’s housework on the other.